The non-standard in writing: A look at West African and Southeast Asian literature - Michael PERCILLIER (E-REA)
The present paper investigates the representation of non-standard varieties of English in literary texts. Using a corpus-based approach focussed on Southeast Asian and West African texts while also drawing on texts from Scotland for purposes of comparison, the study performs a quantitative analysis that empirically defines linguistic feature profiles, revealing that the regions under investigation follow clearly distinct patterns, albeit with a common underlying principle. A diachronic investigation of these linguistic feature profiles shows that far from being static or stable, practices of representation vary from decade to decade.